Effect of head nurse empowerment program on staff nurses' job satisfaction at two educational hospitals in Rasht, Iran - Mohammad Babaeipour-Divshali; Fatemeh Amrollahimishavan; Zohre Vanaki; Abdolghani Abdollahimohammad; Mohammadreza Firouzkouhi (Wolters Kluwer Medknow Publications, 2016)
Background: Job satisfaction of nurses is an important concept in nursing profession because it influences nursing care. Head nurses play a crucial role in the job satisfaction of nurse staffs. The current study, therefore, aimed to investigate the effect of Head Nurse Empowerment Program (HNEP) on job satisfaction of nurses. Materials and Methods: This quasi-experimental study was conducted at two educational hospitals in Rasht, Iran. Of 160 staff nurses who were working in eight medical-surgical wards and two Intensive Care Units, 60 were recruited using simple random sampling method. The samples were randomly assigned to control and experimental groups. The HNEP was applied to promote the management skills among nurses, which included technical, communicational, perceptional, and diagnostic skills. The data were collected using nurses' job satisfaction questionnaire and analyzed using the Mann-Whitney and Wilcoxon Singed Ranks tests. P < 0.05 was set as the significance level. Results: There was a significant difference in the job satisfaction of nurse staff within the experimental group on comparing pre- and post-HNEP phases [78 (65.50) vs. 78 (65.50); P < 0.001]. The job satisfaction also differed between the control and experimental groups [60 (82.25) vs. 128.5 (51.75); P < 0.001]. However, no significant difference [62 (78.75) vs. 60 (82.25); P = 0.129] was found within the control group. The number of satisfied nurse staffs increased in the experimental group from approximately 25% to 76% after HNEP. Conclusions: The HNEP can be used as a promoting tool in the nursing profession. Increasing head nurses' management skills can result in job satisfaction among the staff nurses.